56‐1: High Performance Liquid Crystals for Vehicular Displays. Issue 1 (May 2016) - Peng, Fenglin; Huang, Yuge; Gou, Fangwang; Hu, Minggang; Li, Jian; An, Zhongwei; Wu, Shin‐Tson
Abstract : We report two new liquid crystal mixtures with high clearing point, small visco‐elastic coefficient and low activation energy. With overdriving and undershooting approach, the response time is less than 10ms for FFS LCDs at T=0°C and TN at 20°C. Therefore, these mixtures greatly improve the performances of vehicle displays at extreme environments.